(untitled) (Economic and Political Thought, 2014)
The issue of labour markets has been of interest not only to the theory of economics but also the economic policy practice for years. The importance of this issue results mainly from a common phenomenon of unemployment and its economic and social dimensions. With the occurrence of rising unemployment in the world, special attention was paid to institutional factors influencing labour markets, such as a statutory minimum wage, labour-related tax, labour law regulations and a model of negotiating remuneration. Several years after the introduction of the first minimum wage regulations, a call for raising a minimum wage is still a popular topic of public debate in many countries. Participation in this debate, however, requires understanding of the dependencies and the influence of a minimum wage on a labour market. The article aims to present the dependencies and consequences of the use of a minimum wage. The successive parts of the article present facts and data regarding a minimum wage in particular countries, a theoretical description of a minimum wage and an analysis of the influence of a minimum wage on a labour market. The examination of the influence of a minimum wage on a labour market is conducted from the point of view of the influence of this instrument based on the size of a labour market, i.e. the level of employment and unemployment as well as the differentiation of remuneration in the economy.